Pioneers Of Iraq in the Science of Religion, a Systematic Presentation - Attia , Hoda; marhun, rahim (Islamic Sciences Journal, 2023)
In the name of God, praise be to God, and may peace and blessings be upon the best of God’s creation, Muhammad, his family, companions, and those guided by his guidance. The research sheds light on the effort of Iraqi researchers, Muslims and others in the science of religion, through extrapolating their findings, which include scientific literature in this field, and classifying them according to their methodologies, in order to see what the Iraqi firefly is, who is still creative in the various types of different sciences, stands for the greatness and tolerance of Islam Islamic thought assimilates all sciences as evidenced by the capacity of Islamic production in this field and the multiplicity of scientific methods used in the writings of Muslims